KEDISIPLINAN DAN FASILITAS BELAJAR TERHADAP PRESTASI BELAJAR ILMU PENGETAHUAN SOSIAL - Lilly Dwi Wulandari (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2019)
The purpose of study was to determine how much influence the discipline and student learning facilities have on Social Science learning achievement at SMPIT in Depok City. The research method used in this study is a survey method with correlational analysis. Based on data analysis and the results of hypothesis testing it can be concluded that: There is a significant influence of discipline and learning facilities together on the Social Science learning achievement of SMPIT students in Depok City. This is evidenced by the acquisition of sig value of 0,000 <0.05 and Fcount = 75.161, There is a significant influence of discipline on the Social Science learning achievement of SMPIT students in Depok City. This is evidenced by the acquisition of Sig = 0,000 <0.05 and tcount = 4,391, There is a significant effect of learning facilities on the Social Science learning achievement of SMPIT students in Depok City. This is evidenced by the acquisition of Sig = 0,000 and t = 3,805. The multiple regression relationship is linear with the equation model ? = 36.444 + 0.275 X1 + 0.327 X2. The contribution of each independent variable to the dependent variable is: a) Discipline variable of 0.275, b) Student learning facility variable of 0.327. The contribution of the two independent variables together to the dependent variable is 72.5%. By knowing the contribution of disciplinary variables (X1) and learning facilities (X2) of 27.5% to Social Science learning achievement, it can be concluded that 27.5% of Social Science learning achievement is caused by other factors.